KRAS Mutation Status in Colorectal Epithelial Tumors of Colorectal Cancer - Chakraborty, Amit; Dey, Soumit; Ghatak, Ishita; Ray, Pranamita; Bhattacharya, Subhasree; Sengupta, Archana (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: Colorectal cancer (CRC) is one of the commonest malignancies in industrialized nations with lower incidence in Asia and Africa. Majority of CRCs are non-hypermutated. KRAS is one of the commonest mutated genes in CRC patients. Given the KRAS mutated CRCs are resistant to EGFR targeted chemotherapy, expanded KRAS mutation testing is recommended before starting chemotherapy. The aim of this study was to study the genetic variation of KRAS in group of CRC cancer patients referred to a teaching hospital in Kolkata, India. Methods: Out of 15 cases of colorectal cancer studied, 2 specimens were right hemicolectomies for clinically diagnosed colon carcinomas and 13 specimens were biopsies of colonoscopy done for anaemia, changed bowel habit, occult bleeding. Formalin fixed paraffin embedded (FFPE) tissue sections, stained by routine Hematoxylin and Eosin were examined microscopically. The DNA was extracted from FFPE tissue with Qiagen kit. KRAS Mutation analysis was done by TheraScreen – KRAS Mutation Kit. Results: The age of patients ranged from 28 to 64 years. Nine were male and remaining 6 were female. histopathological examination revealed 10 adenomas and 5 adenocarcinomas. One adenoma, tubulovillous with high grade dysplasia featured positive KRAS mutation (Gly12Asp). Three out of 4 adenocarcinomas with positive KRAS mutation, one showed Gly12Ala and 2 showed Gly12Asp. Conclusion: The frequency of KRAS mutations was very low in the studied sample.